The yield of edible caterpillars Imbrasia oyemensis and Cirina forda from timber trees logged on concessions in the Democratic Republic of the Congo: A contribution to managing tropical forests for multiple resources - Muvatsi, P.; Snook, Laura K.; Morgan, G.; Kahindo, J.M. (Elsevier, 2021)
Local people in rural areas of the tropics depend on forests for a range of food resources, including protein-rich edible caterpillars, among them Imbrasia oyemensis and Cirina forda, which are important for nutrition and income. Sapelli (Entandrophragma cylindricum), the African mahogany, and Tali (Erythrophleum suaveolens) are food sources for these caterpillars; they are also among the most important timber species harvested from Congo Basin forests. This study quantified the yield of caterpillars from harvestable and precommercial sizes of trees of these two timber species to better understand the impact of logging on the availability of edible caterpillars to local people, and the implications for managing both timber and non-timber resources in industrial timber concessions. Caterpillars were collected and weighed beneath 50 Sapelli trees 23–190 cm DBH and 170 Tali trees 22–174 cm DBH on two timber concessions, from mid-August to mid-September, over two years. Caterpillars were found to descend from the trees during 5 days each year, and quantities varied between years. In both sample years, yields were significantly higher from harvestable trees larger than the minimum cutting diameter than from precommercial trees. Each harvestable Sapelli tree (≥ 80 cm DBH), yielded an average of 11.3 kg fresh weight of I. oyemensis year-1; smaller, precommercial trees yielded 5.4 kg tree−1year−1. Each harvestable Tali tree (≥ 60 cm DBH) yielded an average of 9.1 kg of C. forda year−1, as compared to 5.7 kg tree−1year−1 from precommercial trees. This means that industrial timber harvesting, which removes trees larger than the minimum cutting diameter, has a disproportionate effect on the availability of caterpillars. However, trees below the minimum cutting diameter also yield caterpillars, and may occur at higher densities. Guidelines that limit harvesting on steep slopes or near watercourses, or that call for retaining large trees as seed sources, also safeguard caterpillar yields. However, multiple resource management should consider proactive measures, which could include zoning areas near villages as sources of edible caterpillars, and protecting those trees from logging.